Bela bartók’s polymodal chromaticism in chick corea’s children song no.5 and no.15 - Ganesan Balakrishnan; Lee Chie Tsang Isaiah (Penerbit Universiti Malaysia Sabah, 2023)
This study focuses on the application of Bela Bartók’s theory of polymodal chromaticism in Chick Corea’s selected piano pieces from Children’s Songs, 1984. The selected pieces of Children Song No.5 and No.15 provide examples of the application of Bela Bartók’s theory of polymodal chromaticism as a compositional device in jazz music. Despite the significance of these pieces, there exists a scarcity of musical analyses examining the use of polymodal chromaticism, indicating a need for further research in this area. This study reveals the compositional method, style, and tool that Corea uses in applying the theory of polymodal chromaticism. Integration of polymodal chromaticism with functional harmonic progression and unique combinations of modal and compound scales that Corea employs to achieve polymodal chromaticism is revealed in this study. Qualitative method of music analysis and quasi-`Schenkerian music analysis were applied to highlight modal and compound scales, ostinatos, harmonic progression, and compositional techniques Corea used in developing polymodal chromaticism in the selected pieces. The study led to detailed insights into the compositional techniques used to achieve polymodal chromaticism, as well as the discovery of unique compound scales and combinations of scales that led to chromaticism. The methods of applying polymodal chromaticism are detailed in this study, allowing further exploration of the theory in other areas of jazz and contemporary music.